Thermal comfort in interiors and exteriors of educational space in warm semi-dry climate - Martín del Campo Saray, Francisco José (2020)
In the region of El Grullo, Jalisco, Mexico, there are conditions of warm semi-dry climateand according to a review of the SEMARNAT literature (2010), this type of climate occursin 7% of the Mexican territory. This led to a study of thermal comfort in interiors andexteriors of an educational space. The objective of the research was to estimate the valueof neutrality and the comfort ranges of variables of the thermal environment and of theuser to know the sensation and thermal perception of its occupants. A descriptive, nonexperimentaland cross-sectional methodology was used, after a bioclimatic diagnosis. For this, 300 questionnaires were applied for inhabitants and thermal environment in the hot and cold period. Pearson’s correlation was used to know the significant association between meteorological and ordinal variables. The results of the study indicate that in the area of thermal sensation in statistical terms there is a significant association of moderate level with the variable of dry bulb temperature, black globe temperature and weak level with relative humidity. Likewise, the temperature tolerance was significant at a weak level with the black globe temperature and solar radiation.